Genomic analysis of the causative agents of coccidiosis in domestic chickens - Reid, Adam J.; Blake, Damer P.; Ansari, Hifzur R.; Billington, Karen; Browne, Hilary P.; Bryant, Josephine; Dunn, Matt; Hung, Stacy S.; Kawahara, Fumiya; Miranda-Saavedra, Diego; Malas, Tareq B.; Mourier, Tobias; et al. (Genome Research, 2014)
Global production of chickens has trebled in the past two decades and they are now the most important source of dietary animal protein worldwide. Chickens are subject to many infectious diseases that reduce their performance and productivity. Coccidiosis, caused by apicomplexan protozoa of the genus Eimeria, is one of the most important poultry diseases. Understanding the biology of Eimeria parasites underpins development of new drugs and vaccines needed to improve global food security. We have produced annotated genome sequences of all seven species of Eimeria that infect domestic chickens, which reveal the full extent of previously described repeat-rich and repeat-poor regions and show that these parasites possess the most repeat-rich proteomes ever described. Furthermore, while no other apicomplexan has been found to possess retrotransposons, Eimeria is home to a family of chromoviruses. Analysis of Eimeria genes involved in basic biology and host-parasite interaction highlights adaptations to a relatively simple developmental life cycle and a complex array of co-expressed surface proteins involved in host cell binding.